KAJIAN HUBUNGAN KUAT LENTUR DENGAN KUAT TEKAN BETON - Suhendra Suhendra (Universitas Batanghari, 2017)
Currently, rigid pavement in almost all national, provincial and district roads is used instead of flexible pavement. One of the rigid concrete pavement quality controls is the flexural strength (fr = 45 kg / cm2 at 28 days) as stated in the General Specification of Binamarga year 2010 revision 3. This specification no longer regulates the value of compressive strength of the rigid pavement. This is a challenge for the construction’s practicians in implementation of the specification, because during this time the procurement of cement concrete is based on the compressive strength. The formula is in SNI 2847: 2013 on concrete that fr = 0,62Öfc’. While the construction practitioners generally still use the binamarga specifications of previous revisions that contain the quality of concrete (K-350), so that the quality of bending in general is not achieved. This research covers the value of bending test results conducted in the Engineering Laboratory on beams provided by third parties using lab services, as well as test specimens made in the laboratory. The test results show that there is a correlation between the flexure strength to the compressive strength of the concrete. The relationship is more or less the same as the formula contained in SNI concrete.Keywords: Concrete, Flexure strength, compressive strength, Binamarga Specs 2010 rev. 3